Что такое существительное? - Шалаева Галина Петровна (Маленький гений, 2010)
Экземпляры: ф.4 (2011) / Инвентарный номер: 53919 / Цена: / Сис.шифр: 81.2Рус / Авт.знак: Ш 18 / ГРНТИ: 16.21.41 / ББК: 81.2Рус-9